Green Intellectual Capital, Performance, and Research Agenda - Hariyanto, Wiwit; Sigit Hermawan; Sriyono (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2025)
Study This aim For explore the relationship between Green Intellectual Capital and financial, non-financial performance and opportunities research coming through approach bibliometrics . Analysis done of the 122 publications obtained from the Scopus database in the 2019-2024 period . Research result show trend increase interest towards GIC, especially in 2023. Countries such as China, Pakistan and Malaysia are becoming center study main . Journal Journal of Intellectual Capital be the most productive in publish study related to GIC. Keyword analysis​ show that concepts like sustainability , green innovation , and knowledge management are closely related with GIC. Additionally , research​ this also identifies writers , articles , and networks the most influential collaboration in field This . Research result This give more understanding​ comprehensive about development GIC research , identify gap research , and highlighting opportunity For study more carry on . Findings This can become guide for researchers , practitioners , and makers policy in develop more strategies effective For reach sustainability